Spekulatif Arah Politik Hukum Kepariwisataan Di Indonesia Dari Pengembangan Community Base Tourism - Dhoni Martein; Dhian Tyas Untari; Desyana Berliana; Iswiyati Kunti; Tiara Yuliana Wanti; Wiky Rikamza (Jurnal Kajian Ilmiah, 2021)
Tourism is a non-oil and gas sector with a fairly high development potential, even the tourism sector makes a large contribution to GDP and GRDP. According to the Law of the Republic of Indonesia Number 10 of 2009 concerning Tourism and the Regulation of the Minister of Home Affairs Number 33 of 2009 concerning Guidelines for Ecotourism Development in the Regions, it is stated the importance of community participation in tourism development. Based on this, this study aims to; 1). Studying the political direction of tourism law in Indonesia, 2). Mapping the internal and external environment for Community Base Tourism (CBT) development, and 3). Develop speculative hypotheses related to the CBT development strategy. This study is sourced from secondary data from books and publications related to Tourism Law Politics and CBT Development. The analysis used is the Strategic Management matrix; EFAS/IFAS and Garnd Matrix. The results of the study are expected to become an umbrella for research related to the development of CBT in the perspective of Political Law.